2013
DOI: 10.1371/journal.pone.0080037
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Contextual Fear Conditioning in the Rat

Abstract: In contextual fear conditioning (CFC) a single training leads to long-term memory of context-aversive electrical foot-shocks association. Mid-temporal regions of the brain of trained and naive rats were obtained 2 days after conditioning and screened by two-directional suppression subtractive hybridization. A pool of differentially expressed genes was identified and some of them were randomly selected and confirmed with qRT-PCR assay. These transcripts showed high homology for rat gene sequences coding for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The effect of GR phosphorylation on this serine is gene-silencing (Wang et al, 2002;Schoneveld et al, 2004;Galliher-Beckley and Cidlowski, 2009;Hudson et al, 2013). Different molecular techniques to measure changes in gene expression have been shown that one of the first molecular events that occurs in the acquisition of CFC is inhibition of gene expression in the hippocampus, including those genes that are regulated by the GR (angiotensinogen, mineralocorticoid receptor, some ribosomal proteins, lactate dehydrogenase B, and monoamine oxidase A among others), especially within the first 60 min after training or administration of CORT (Morsink et al, 2006;Federighi et al, 2013;Cho et al, 2015). However, these reports did not localize the effect of training on gene-silencing within the different hippocampal subregions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GR phosphorylation on this serine is gene-silencing (Wang et al, 2002;Schoneveld et al, 2004;Galliher-Beckley and Cidlowski, 2009;Hudson et al, 2013). Different molecular techniques to measure changes in gene expression have been shown that one of the first molecular events that occurs in the acquisition of CFC is inhibition of gene expression in the hippocampus, including those genes that are regulated by the GR (angiotensinogen, mineralocorticoid receptor, some ribosomal proteins, lactate dehydrogenase B, and monoamine oxidase A among others), especially within the first 60 min after training or administration of CORT (Morsink et al, 2006;Federighi et al, 2013;Cho et al, 2015). However, these reports did not localize the effect of training on gene-silencing within the different hippocampal subregions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our work is in agreement with Fanara et al 49 whose study implicates microtubule turnover in learning. A recent study has shown that the levels of stathmin mRNA and protein are increased two days following contextual fear conditioning 50 . It is possible that the increases in stathmin levels found in that paper reflect the compensational changes caused by the earlier use of stathmin on day one following learning as our work demonstrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that the total levels of stathmin mRNA and protein in the dentate gyrus of the rat hippocampus are increased 48 h following contextual fear conditioning (Federighi et al, 2013). This finding suggests that following learning stathmin may be involved in other intracellular processes in addition to the synapse-specific events (Uchida et al, 2014).…”
Section: Biphasic Changes In Stathmin Activity Following Learningmentioning
confidence: 99%